Konsep dan Peran Uang dalam Perspektif Ekonomi Islam - Nasywa Putri Tsabitah; Muhammad Nurfauzi Maliki; Nava Diah Neviana; Regina Yuniar Lestari; Amalia Nuril Hidayati (Journal Economic Excellence Ibnu Sina, 2024)
This research examines the concept of money from an Islamic economic perspective which is fundamentally different from conventional economic views. In Islam, money is not a commodity that can be traded for profit. Money is a medium of exchange that must be used to support real economic activities and contribute to social welfare. The basic principles of Islamic economics, such as the prohibition of usury, gharar, and maysir strictly regulate the use of money so that it cannot be used for speculative activities that have the potential to be detrimental. This research aims to analyze the role of money in Islamic economics, explore its application in the Islamic financial system, and assess its impact on wealth distribution and economic stability. The research results show that the concept of money in Islam emphasizes justice, ethics and balance in the economy, and can provide a more sustainable alternative compared to conventional financial systems which often pursue maximum profits without paying attention to social impacts. This research concludes that the application of money principles in Islamic economics can support the creation of a fairer and more inclusive financial system and contribute to the overall economic welfare of the people.